2007
DOI: 10.2209/tdcpublication.48.177
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Effects of X-Ray and Carbon Ion Irradiation in Head and Neck Carcinoma Cell Lines

Abstract: The effects of X-ray and carbon ion irradiation on DNA and genes in head and neck carcinoma cells were examined. Four head and neck cancer cell lines (squamous cell carcinoma, salivary gland cancer, malignant melanoma, normal keratinocyte) were treated with 1, 4, and 7 GyE of carbon ion, or 1, 4, and 8 Gy of X-ray, respectively. DNA and RNA in the treated cells were extracted and purified. PCR-LOH (polymerase chain reactionloss of heterozygosity) analysis with 6 microsatellite regions on chromosome 17 was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Their formation results from constitutional and/or inherited factors combined with environmental factors. Skin carcinoma are usually treated by surgical excision [2], radiotherapy [3][4][5], irradiation [6] or dynamic phototherapy [7]. However, these treatments are painful and invasive.…”
Section: Introductionmentioning
confidence: 99%
“…Their formation results from constitutional and/or inherited factors combined with environmental factors. Skin carcinoma are usually treated by surgical excision [2], radiotherapy [3][4][5], irradiation [6] or dynamic phototherapy [7]. However, these treatments are painful and invasive.…”
Section: Introductionmentioning
confidence: 99%
“…Examining X-ray and carbon ion induced effects on DNA in head carcinoma cells by using PCR of heterozygosity, Yamamoto et al observed that most of the X-ray induced DNA damage occurred in the target region on one of the homologous chromosomes, whereas carbon ions caused homo-deletion, i.e. deletion of the counterparts in both homologous chromosomes [51]. …”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, it has been found that the survival fraction of cancer cells with carbon beam was lower than that of X-rays with same does, indicating that the carbon beam may have advantages over X-rays in radiotherapy 2,3,28. Although many studies have reported the changes of phenotype underlying different types of radiation, the molecular mechanism is still pending to be clarified to improve radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although X-rays treatment is an effective modality for variety of human cancers, in certain cases it can provide poor results 1. Some studies report that heavy ion beam have obvious advantages over other radiotherapy mainly due to the spread out Bragg’s peaks (SOBP), which can cover tumors with biological equivalent dose distribution 2,3. Besides, heavy ion can also reduce oxygen enhancement ratio, decrease cell-cycle-dependent radiosensitivity, and induce more DNA double strand breaks that are not easily repaired 46.…”
Section: Introductionmentioning
confidence: 99%